Optimalisasi Penggunaan Internet Dan Media Pembelajaran Pada Guru Madrasah Di Kecamatan Glagah Kabupaten Banyuwangi - Susintowati; Prasetiyo, Totok Hari; Mahfud; Dian Arief Pradana; St. Shabibatul Rohmah; Sahru Romadloni (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2023)
There is no doubt that optimizing the internet and learning media has a positive impact on student performance and learning achievement. Learning in the post-pandemic transition period also requires optimizing the use of the internet and interactive learning media so that learning can run according to the desired targets and catch up during the pandemic. This technical guidance was carried out at Cawan View Resto which is located in Glagah District, Banyuwangi Regency and was attended by madrasa teachers in the district. The presentation of the material was carried out by FKIP lecturers at the University of 17 August 1945 Banyuwangi and the material was divided into material about PTK and its implementation, material about learning strategies and models, material about interactive learning media, and technical guidance for PTK and Learning Media as well as structured assignments. The training was carried out using lecture and discussion methods and from the results of the training it was concluded that this training provided participants with additional knowledge about the material mentioned above which could be applied in the classroom and produce PTKM reports which could be published and could increase the performance points of the participants.